Pour une meilleure évaluation de la compétence lexicale dans les écrits créatifs en FLE - Christèle Maizonniaux (Recherches en didactique des langues et des cultures, 2014)
This article examines the pertinence of the criteria that are usually applied to the evaluation of lexical competency in written language production. It is based on doctoral research undertaken during the first semester of 2009 at The Australian National University (ANU) (Canberra) and highlights the inadequacy of the two criteria of mastery and broadness of the lexical repertoire elaborated in the Common European Framework of Reference for Languages (CEFR) in assessing the extent to which vocabulary acquisition is evidenced through constrained writing exercises that follow on from the reading of iconotexts written originally for children. An additional criterion is proposed in order to emphasise the extent of the linguistic task performed by the student writing in a foreign language and to highlight the individual contribution made by the student in a monomodal piece of writing that displays considerable hybridity.